Effects of consumer demand, product lifetime, and substitution ratio on perishable inventory management - Duong, L.; Wood, Lincoln; Wang, W. (M D P I AG, 2018)
© 2018 by the authors. With the intensification of global population, food security is a big concern. Food waste stems from inappropriate inventory management. Companies offer a wide range of products to capture more sales, yet this increases inventories and complicates inventory management. Management challenges are worsened by three factors: uncertain consumer demand, product lifetimes, and consumer substitution among the product range. This research aims to understand the effects of these factors on inventory performance. The analytic hierarchy process (AHP) method was used to weight the importance of each of the non-financial performance measures from the simulation results and data envelopment analysis (DEA) was used to rank and evaluate the scenarios. Then, the most favorable scenario or replenishment policy, which had the lowest DEA efficiency score, was chosen. The results show that when the substitution ratio is greater, its interaction with consumer demand and product lifetime has mostly a small- or medium-sized effect on retailers' performance, in contrast to relatively larger effects on the supplier. These findings show that suppliers' performance is affected largely by the existence of the bullwhip effect in the model. Recommendations are provided for managers who are facing uncertainties of consumer demand, substitution, and product lifetime.